Η Ευδοκία Μακρεμβολίτισσα και τα νομίσματα του Κωνσταντίνου Ι’ Δούκα - MEŠANOVIĆ, Sanja (Byzantina Symmeikta, 1998)
Sanja Mešanović Eudocia Makrembolitissa and the Coinage of Constantine X Doucas Constantine X Doukas (1059-1067) issued, during his reign, silver and copper coinage bearing the portraits of himself as well as the portraits of his powerful wife Eudocia. Particularly interesting is a copper coin, which breaks the tradition of almost eighty years of purely anonymous issues, having the standing figures of Constantine and Eudocia and the inscriptions Constantine Doukas and Eudocia Augusta Eudocia is occupying, instead of her husband, the place of honor. Until nowadays the presence of the empress Eudocia Makrembolitissa on the coinage of her husband was attributed exclusively to her important political influence. This article argues that the presence of empress Eudocia’s portrait on the copper coinage of Constantine X, together with the title Augusta is due not only to her political influence but probably also to the revival of an old byzantine tradition of the 4th, 5th, and the beginning of the 6th centuries. According to this tradition a Byzantine empress was proclaimed Augusta and had the right to appear on the coinage after giving birth to an heir to the throne. The motive behind this revival of an old and forgotten tradition might have been the attempt to ensure the future of the new dynasty of the Doucas family, which arouse to the throne of the Byzantine Empire in 1059, after a rather long period of political instability and quick changes of emperors, caused by the absence of a male heir of the Macedonian dynasty. Our hypothesis is strengthened by the fact that the appearance of Eudocia’s effigy on the copper coinage of her husband is soon followed by the revival of another old byzantine tradition. This time, in 1068, after Eudocia’s wedding with her second husband Romanos IV Diogenes, a marriage solidus, struck to celebrate the event as well as to legalize the new emperor Romanos IV, was issued. The same practice was exercised in the 5th century during the reign of Theodosios II (408-450), Marcian (450-457) and Anastasios I (491-518).